Robust visual touch-up calibration method in robot laser spot welding application - Rejc, Jure (Strojniški vestnik, 2016)
The article is describing the use of visual touch-up calibration method for defining the mathematical transformations used in a shop- floor measurement and welding robot cell in the protector assembly process. The presented system is designed as a robust and cheap solution, using only the equipment needed for the production tasks in the robot cell. The main goal of the presented system is to use vision measurement system for measuring and calibration procedures and laser welding equipment to weld two protector assembly parts together where positioning tolerances are very narrow. These narrow tolerances forced us to implement auto-checking and auto-calibration procedures for all necessary mathematical aspects in the robot cell, based on the robust visual touch-up method. To demonstrate adequate solution in the measurement, calibration and also the production sequences, the graphs show production statistical results over a one year production period.
Keywords: homogene transformacije; kalibracija; napaka kinematike; robotsko varjenje; video-dotična metoda